Buying Decision Process of Non-Alcoholic Beverages in Modern Trade Store for Consumers in Nonthaburi Province - Tongwassanasong, Nitinop (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2018)
The objectives of this research were to study the level of the buying decision process, and the marketing mix affecting the buying decision process, of non-alcoholic beverages in a modern trade store for consumers in Nonthaburi province. The research instrument was a questionnaire. The sample was 400 consumers that were selected by the accidental sampling method. Data were analyzed by a statistical program. The statistics used in this study were percentage, arithmetic mean, and standard deviation. Multiple linear regression analysis was used to test the hypotheses. The results showed that 1) The level of the buying decision process of non-alcoholic beverages in a modern trade store for consumers in Nonthaburi province was high, 2) The marketing mix in terms of product, price, place and promotion affected the buying decision process for non-alcoholic beverages in a modern trade store for consumers in Nonthaburi province. All independent variables could explain the variation in the buying decision process for non-alcoholic beverages in a modern trade store for consumers in Nonthaburi province at 87.50%.